Reintroduced mowing can counteract biodiversity loss in abandoned meadows - Lundberg, Anders; Kapfer, Jutta; Måren, Inger Elisabeth (ERDKUNDE, 2017)
Habitat loss is one of the primary environmental causes of biodiversity decline across scales; locally to globally. Ecological restoration is acknowledged as an important tool to counteract this negative trend. The semi-natural calcareous sand dune meadows in south-western Norway are known for their high species diversity, much like similar habitats of high conservation value across Europe today. The recent cessation of grazing has caused a decline in several endangered species associated with these habitats due to the advancement of secondary succession. We conducted a long-term restoration experiment in semi-natural dune meadows over 16 years to examine if current trends in biodiversity loss could be reversed and at what time-scale restoration measures take effect. Three treatments were applied; mowing annually, mowing bi-annually, and a control (no mowing). In fields mown annually species richness increased significantly over time. However, the response was slow and significant effects were first seen after year 10. Fields mown bi-annually also showed a similar trend but the response was more variable. Several characteristic meadow species were favoured by annual mowing while they declined in the control fields. Principal component analysis (PCA) revealed a compositional shift, indicating the re-arrangement/-establishment of typical meadow vegetation in the mown sites, contrasting the further successional development in the control. Our results demonstrate the importance of long-term data in supporting good evidence-based management. Annual mowing is effectively restoring this unique habitat, but restoration efforts need to be sustained over many years to show positive effects.